KAJIAN PROSES PENGOLAHAN COKELAT BATANGAN (CHOCOLATE BAR) DI PT XYZ DI KOTA KENDARI - SULAWESI TENGGARA - Dhian Herdhiansyah; Asriani Asriani (Universitas Muhammadiyah Purwokerto, 2022)
This study aims to determine the processing process of chocolate bars in PT XYZ Kendari City - Southeast Sulawesi. The data was collected using observation, interviews, and documentation and then analyzed using qualitative and descriptive approaches. The results showed that the chocolate processing process at PT XYZ Kendari City begins with the post-harvest stage then the next stage is the processing of cocoa paste and chocolate bars and then the cocoa processing process, namely filtering cocoa beans, peeling the cocoa shells using the NSS (Nib Shell Separator), grinding nib into a coarse paste using a stone mill, grinding coarse paste into a fine paste using a ball mill 30, then mixing the chocolate dough in a mixer, mashed chocolate dough using a mini ball mill, molding chocolate using a tempering machine, freezing chocolate into the freezer, and chocolate bar packaging.